2001
DOI: 10.1021/bi010615o
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Dynamics of the Functional Domain of Paracoccus denitrificans Cytochrome c552 in Both Redox States,

Abstract: A soluble and fully functional 10.5 kDa fragment of the 18.2 kDa membrane-bound cytochrome c(552) from Paracoccus denitrificans has been heterologously expressed and (13)C/(15)N-labeled to study the structural features of this protein in both redox states. Well-resolved solution structures of both the reduced and oxidized states have been determined using high-resolution heteronuclear NMR. The overall protein topology consists of two long terminal helices and three shorter helices surrounding the heme moiety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…A similar situation occurs in the homologous HT c 552 and PH c 552 proteins. The increased stability upon one-electron reduction of the present proteins should be attributed to an as-yet undefined local environment near the heme, as observed in Paracoccus denitrificans cyt c. 18) More elaborate microcalorimetry and hydrogen exchange studies of the three cyts c should eventually lead to a dynamic and systematic explanation of the overall stability differences between the two redox forms.…”
Section: Stability Comparison Between the Oxidized And Reduced Formsmentioning
confidence: 72%
“…A similar situation occurs in the homologous HT c 552 and PH c 552 proteins. The increased stability upon one-electron reduction of the present proteins should be attributed to an as-yet undefined local environment near the heme, as observed in Paracoccus denitrificans cyt c. 18) More elaborate microcalorimetry and hydrogen exchange studies of the three cyts c should eventually lead to a dynamic and systematic explanation of the overall stability differences between the two redox forms.…”
Section: Stability Comparison Between the Oxidized And Reduced Formsmentioning
confidence: 72%
“…S1 in the supplemental data) had shown a 20-nm shift of the tryptophan band (42). This is apparently due to an alteration in the electronic structure of Trp 57 , since the protein conformation is identical in both redox states as confirmed by both x-ray and NMR structure analysis (42,43), thus excluding an explanation that is based on conformational changes in the protein structure. Hence, the only distinction that could explain this redox state-dependent effect in the fluorescence spectrum of P. denitrificans cytochrome c 552 is the additional electron delocalized across the porphyrin system.…”
Section: Resultsmentioning
confidence: 92%
“…In the case of P. denitrificans, for example, fluorescence spectra of reduced and oxidized cytochrome c 552 (see Fig. S1 in the supplemental data) had shown a 20-nm shift of the tryptophan band (42). This is apparently due to an alteration in the electronic structure of Trp 57 , since the protein conformation is identical in both redox states as confirmed by both x-ray and NMR structure analysis (42,43), thus excluding an explanation that is based on conformational changes in the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…The three-dimensional structure of R. capsulatus cyt c y is not available, but its amino acid sequence is highly similar (63% identity and 75% similarity over 95 amino acids) to that of cyt c 552 of Paracocus denitrificans of known structure (32,33). A structural model for the cyt c domain of R. capsulatus cyt c y built by homology modeling based on that of cyt c 552 indicated that Lys-19 is on the surface of the protein and solvent exposed, whereas His-53 is slightly buried into the protein (Fig.…”
Section: Discussionmentioning
confidence: 99%